2001
DOI: 10.1111/j.1559-1816.2001.tb00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Technologies for Conception: A 15‐Year Follow‐Up

Abstract: The attitudes of students toward technologies related to conception were assessed in 1984 and again in 1999. It was expected that increased routinization of such technologies over time would result in higher approval ratings in the second survey. This hypothesis was not supported by the results; there were no changes in approval for most methods that were included in both surveys, and in some cases, approval decreased. It was also hypothesized that methods included in the 1984 survey would receive higher appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
1
9
0
3
Order By: Relevance
“…In the studies in which the population’s attitude towards SP (without specifying what subtype) has been collected, this has always been exclusively done in infertility contexts: that is, approached as a type of ART. In spite of that, the surveyed populations in the USA (Dunn et al, 1988; Lasker and Murray, 2001; Weiss, 1992), Germany (Stöbel-Richter et al, 2009) and Sweden (Wennberg et al, 2015) showed differing degrees of unfavourable attitudes towards SP. Canada (Genuis et al, 1993), Japan (Suzuki et al, 2006), the UK (Bruce-Hickman et al, 2009), Iran (Rahmani et al, 2011) and Australia (Constantinidis and Cook, 2012), on the contrary, are countries where the studies’ populations show a high level of acceptance of SP.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies in which the population’s attitude towards SP (without specifying what subtype) has been collected, this has always been exclusively done in infertility contexts: that is, approached as a type of ART. In spite of that, the surveyed populations in the USA (Dunn et al, 1988; Lasker and Murray, 2001; Weiss, 1992), Germany (Stöbel-Richter et al, 2009) and Sweden (Wennberg et al, 2015) showed differing degrees of unfavourable attitudes towards SP. Canada (Genuis et al, 1993), Japan (Suzuki et al, 2006), the UK (Bruce-Hickman et al, 2009), Iran (Rahmani et al, 2011) and Australia (Constantinidis and Cook, 2012), on the contrary, are countries where the studies’ populations show a high level of acceptance of SP.…”
Section: Resultsmentioning
confidence: 99%
“…Casi todos los casos se refieren a población con problemas de fertilidad (Baykal et al, 2008;Bello et al, 2014;Halman et al, 1992;Kilic et al, 2009;Miall, 1989;Rahimi et al, 2016;Rahmani et al, 2011;Saito y Matsuo, 2009), a población de mujeres (Krishnan, 1994;Poote y Akker, 2009;Sardiñas et al, 2014;Wennber et al, 2015), a población de mujeres y hombres sin hijos (Daniluk y Koert, 2012) y a población que ha recurrido o contempla la subrogación (Everingham et al, 2014). Por último, otros trabajos recurren a muestras de conveniencia (selección de los casos por disponibilidad), como los estudios que recogen la opinión de estudiantes (Bruce-Hickman et al, 2009;Constantinidis y Cook, 2012;Dunn et al, 1988;Lasker y Murray, 2001). La investigación recopilada se enmarca, mayoritariamente, en el ámbito clínico.…”
Section: 1cuestiones Generales Sobre El Diseño De Los Estudiosunclassified
“…De hecho, quince estudios preguntaban explícitamente, o a través de los contextos que exponían, sobre esta técnica. En siete investigaciones se interrogaba a la población por ambos tipos de subrogación y en todas ellas se muestra la preferencia por la subrogación gestacional (Constantinidis y Cook, 2012;Dunn et al, 1988;Halman et al, 1992;Lasker y Murray, 2001;Saito y Matsuo, 2009).…”
unclassified
See 1 more Smart Citation
“…The majority of the various samples have negative or agnostic attitudes toward gestational surrogacy (Japan being the exception) (Baykal et al,. 2008;Kovacs et al, 2003;Lasker and Murray, 2001;Suzuki et al, 2011). If focusing on surveys on commercial surrogacy, an increase in negative attitudes is 4 reasonable to expect (Krishnan, 1994).…”
Section: Surrogacy and The Harm Argumentmentioning
confidence: 99%